Feasible fabrication of durable superhydrophobic SiO2 coatings with translucency and self-cleaning performance. (16th October 2020) - Wang, Chenxiang; Tian, Feng; Zhang, Xuefen
Abstract: In this work, a versatile strategy was proposed to fabricate translucent superhydrophobic coatings by spraying the suspension of modified SiO2 /polydimethylsiloxane (PDMS) on various substrates. The wettability can be adjusted by changing the mass ratio of modified SiO2 nanoparticles in the suspension. By optimizing the parameters in the spraying process, a superhydrophobic surface with a water contact angle of 164.1 ± 3.4° and a sliding angle of 4.2 ± 0.4° was achieved. As prepared translucent superhydrophobic SiO2 /PDMS coatings show good mechanical durability, chemical stability, and self-cleaning performances.